Factors That Influence the Documentation of the Completeness of Nursing Care by the Implementing Nurse in the Emergency Room at Anutapura General Hospital, Palu. - Dwi Fatmawati; Ismawati Ismawati; Nelky Suriawanto (Institute of Computer Science (IOCS), 2018)
The Nursing documentation that done is still incomplete, especially in evaluation notes and nurses notes. Incomplete patient file will have an impact on the quality of hospital services and legal ethical issues the purpose of this study is to obtain factors of documentation of the completeness of nursing care that done by staff nurse in the emergency room of Anutapura General Hospital Palu. This type of research is quantitative, with observational analytic cross sectional approached. Sampling numberwas total of population about 31 staff nurse. Data analysed by used chi-squer test with Fisher's Exact Test alternative test at significante level (ɑ <0.05). The results of the research on the level of good knowledge with the complete documentation category 91.3%, the level of poor knowledge category of incomplete 75.0%. and high workload with a complete documentation category about 40.0%, low workload with a complete documentation category about 9.5%. knowledge with the completeness of nursing care as a result of Fisher’s Exact Test alternative test results obtained P-value 0.015 (p <0.05), and workload with complete documentation of the results of Fisher’s Exact Test alternative test obtained P-value 0.002 (p <0.05). conclusion there is a relationship between workload, knowledge with the completeness of nursing care. Suggestions for the hospital to evaluate the workload efforts experienced by nurses in the emergency room so that documentation of nursing care conld be qualified for patient services.